Pengaruh Struktur Kepemilikan Institusional, Kepemilikan Manajerial, Kepemilikan Keluarga, Pengungkapan Sukarela Dan Leverage Terhadap Biaya Utang - Pebrina swissia; Benri Purba (Jurnal Akuntansi dan Keuangan, 2018)
The objective of this research was to prove empirically the effect of the institutional ownership structures, the managerial ownership, the family ownership, the voluntary disclosure, and leverage on the debt cost. There were 5 independent variables used in this research i.e., the institutional ownership, the managerial ownership, the family ownership, the voluntary disclosure, and the leverage. Moreover, the dependent variable used in this research was the debt cost. The population of this research was the manufacturing companies indexed in Indonesia Stock Exchange in the period of 2014-2016. The sampling technique used in this research was the purposive sampling. The number of samples used in this research was 28 companies. The observation was done to the companies in 2014-2016, so that the number of collected data was 84 data. The data analysis technique used in this research was the multiple linear regression with SPSS v.20 tool. The result of this research showed that the institutional ownership, the managerial ownership, the family ownership affected the debt cost; while, the voluntary disclosure and the leverage did not affect the debt cost.